2021
DOI: 10.3389/fonc.2020.580128
|View full text |Cite
|
Sign up to set email alerts
|

Operative and Oncological Outcomes Comparing Sentinel Node Mapping and Systematic Lymphadenectomy in Endometrial Cancer Staging: Meta-Analysis With Trial Sequential Analysis

Abstract: ObjectiveTo evaluate the utility of sentinel lymph node mapping (SLN) in endometrial cancer (EC) patients in comparison with lymphadenectomy (LND).MethodsComprehensive search was performed in MEDLINE, EMBASE, CENTRAL, OVID, Web of science databases, and three clinical trials registration websites, from the database inception to September 2020. The primary outcomes covered operative outcomes, nodal assessment, and oncological outcomes. Software Revman 5.3 was used. Trial sequential analysis (TSA) and Grading of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Mayo Clinic analyzed 378 patients and found that SLN may significantly decrease the risk of lymphedema compared with LAD (26.0% vs. 49.4%, p<0.001) (96). Several meta-analyses included current retrospective and prospective studies presented similar conclusions, which was SLN resulted in less blood loss, lymphedema, and other complications, meanwhile, SLN detected more pelvic metastasis (97,98). These results may indicate that SLNM is able to minimize the surgical risk and reduce the complications with no survival detriment in EC, which is of great value to improve the quality of life.…”
Section: Slnm Reduced Intraoperative and Postoperative Complicationsmentioning
confidence: 94%
“…Mayo Clinic analyzed 378 patients and found that SLN may significantly decrease the risk of lymphedema compared with LAD (26.0% vs. 49.4%, p<0.001) (96). Several meta-analyses included current retrospective and prospective studies presented similar conclusions, which was SLN resulted in less blood loss, lymphedema, and other complications, meanwhile, SLN detected more pelvic metastasis (97,98). These results may indicate that SLNM is able to minimize the surgical risk and reduce the complications with no survival detriment in EC, which is of great value to improve the quality of life.…”
Section: Slnm Reduced Intraoperative and Postoperative Complicationsmentioning
confidence: 94%
“…Additionally, cervical injection increases the bilateral sentinel lymph node detection rate but decreases the para‐aortic detection rate compared with alternative injection techniques. A meta‐analysis pooling approximately 6000 patients suggests that sentinel lymph node mapping is more targeted for less node dissection and more detection of positive lymph nodes even in high‐risk patients 76 . Since sentinel lymph node mapping can safely replace lymphadenectomy in the staging of endometrial cancer, it is becoming the preferred method for lymph node sampling, even in high‐risk cancer.…”
Section: Is Lymphadenectomy Therapeutic?mentioning
confidence: 99%
“…A meta‐analysis pooling approximately 6000 patients suggests that sentinel lymph node mapping is more targeted for less node dissection and more detection of positive lymph nodes even in high‐risk patients. 76 Since sentinel lymph node mapping can safely replace lymphadenectomy in the staging of endometrial cancer, it is becoming the preferred method for lymph node sampling, even in high‐risk cancer. However, side‐specific systematic lymphadenectomy should be performed in high intermediate‐risk/high‐risk patients if the sentinel lymph node is not detected on either pelvic side.…”
Section: Is Lymphadenectomy Therapeutic?mentioning
confidence: 99%
“…During reduction process, the input dataset is provided to the MapReduce data thereby splitting into independent data by employing map process. 38 The output obtained in the map task is provided as an input of the map reduce task. The map functions implement the allocation process of every data sample to the neighboring focus and at the same time, the map reduce task accomplishes the updating of new centers.…”
Section: Reduction Processmentioning
confidence: 99%